2014
DOI: 10.1002/adfm.201304312
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Prodrug Therapy Engineered into Biomaterials

Abstract: In this work, enzyme-prodrug therapy (EPT) is engineered into hydrogel biomaterials to achieve localized synthesis of the drugs and their delivery to the adhering cells. The use of EPT in the context of drug delivery mediated by biomaterials signifi cantly empowers the latter in that the same hydrogel is used to successfully synthesize several drugs with dissimilar structures and therapeutic effects. The concentration of the synthesized drugs is conveniently controlled by the concentration of the administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…Enzyme prodrug therapy (EPT) is a versatile technique that allows synthesis of drugs at the site of action when prodrugs were systemically administrated [25][26][27]. In addition to targeted and localized drug delivery, the advantage of EPT also includes the fine tune of drug dosage, duration, and administration [28].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme prodrug therapy (EPT) is a versatile technique that allows synthesis of drugs at the site of action when prodrugs were systemically administrated [25][26][27]. In addition to targeted and localized drug delivery, the advantage of EPT also includes the fine tune of drug dosage, duration, and administration [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bioconjugation of lysozyme to the PVA hydrogel was further analyzed with regards to the enzymatic activity of the sample. Activity of this protein is important in biomedicine as part of antibacterial treatment mediated by the biomaterial [46] and also for applications in surface mediated drug delivery, specifically through an in situ synthesis of drugs from the externally administered prodrugs [45,47]. Herein, enzymatic activity of lysozyme was used to quantify the catalytically active fraction of the immobilized protein.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, hydrogels are implantable materials that can deliver large amounts of enzymes locally, which enhances the therapeutic effect. In a seminal study, Mendes and Zelikin developed biocatalytic hydrogels based on poly(vinyl alcohol) (PVA) with embedded β‐Glu for substrate‐mediated DDSs ( Figure ) . They showed that hydrogels with entrapped β‐Glu could convert three different anticancer prodrugs to cytotoxic drugs in HepG2 cell culture media, leading to an antiproliferative effect.…”
Section: Design Strategies and Functions Of Biocatalytic Reactorsmentioning
confidence: 99%
“…A) Schematic diagram of structure of enzyme‐functionalized physical hydrogels based on poly(vinyl alcohol) and differential interference contrast image of hydrogels and B) chemical structures of glucuronide‐modified prodrug and native drug, and viabilities of hepatocyte cells cultured in presence of prodrugs and β‐Glu‐loaded hydrogels. Reproduced with permission . Copyright 2014, Wiley‐VCH.…”
Section: Design Strategies and Functions Of Biocatalytic Reactorsmentioning
confidence: 99%